The occurrence of Anaplasmataceae in European populations of invasive carnivores - Hildebrand, Joanna; Buńkowska-Gawlik, Katarzyna; Adamczyk, Maja; Gajda, Ewa; Merta, Dorota; Popiołek, Marcin; Perec-Matysiak, Agnieszka (Ticks and tick-borne diseases, 2018)
The raccoon (Procyon lotor) and the raccoon dog (Nyctereutes procyonoides) belong to a group of the invasive species. The introduced species as potential reservoirs for vector-borne pathogens have been the subject of recent research, though there are still no data with reference to the European population of the raccoon, and few studies concern only the raccoon dog. This study shows the occurrence of Anaplasmataceae representatives in raccoons and a sympatric population of the raccoon dogs obtained from the area of Poland and Germany. During the study, the occurrence of Anaplasma phagocytophilum ecotype I in the introduced raccoon in northwestern Poland was revealed. Additionally, Candidatus Neoehrlichia sp. (FU98) was identified for the first time in the raccoon dog in Central Europe and thereby the raccoon dog is a new host for this pathogen.